Islamic Religious Education Teachers’ Strategies in Fostering Students’ Religious Values in Madrasah - HM. Ridlwan Hambali; Dadan Rusmana; Siti Saodah Susanti; Khermarinah Khermarinah; Fakhrurrazi Fakhrurrazi (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to identify the strategies of Islamic Religious Education (PAI) teachers in fostering students’ religious values in madrasas as well as to evaluate supporting and inhibiting factors experienced by the teachers. This study used literature study as the research method. Ten articles were taken as the data of this study. To analyze the data, content analysis was implemented. The findings reported that PAI teachers used expository strategies for developing students’ religious values in madrasas. The development of religious values is divided into three types, namely the formation of faith, the formation of worship, and the formation of morals. PAI teacher strategies in fostering religious values are in the form of doing religious activities, such as istighasah, dhuha prayer, reading prayers before and after studying, and reading the quran. Supporting factors for the strategy of fostering religious values in madrasas are the increasing interest of students in the religious field, cooperation between teachers, and well-functioning madrasa regulations.